Classification of Trispanins: A Diverse Group of Proteins That Function in Membrane Synthesis and Transport Mechanisms - Attwood, Misty M.; Schiöth, Helgi B. (Frontiers in Cell and Developmental Biology, 2020)
As the structure and functions of proteins are correlated, investigating groups of proteins with the same gross structure may provide important insights about their functional roles. Trispanins, proteins that contain three alpha-helical transmembrane (3TM) regions, have not been previously studied considering their transmembrane features. Our comprehensive identification and classification using bioinformatic methods describe 152 3TM proteins. These proteins are frequently involved in membrane biosynthesis and lipid biogenesis; protein trafficking; catabolic processes, and in particular signal transduction due to the large ionotropic glutamate receptor family. Proteins that localize to intracellular compartments are overrepresented in the dataset in comparison to the entire human transmembrane proteome, and nearly 45% localize specifically to the endoplasmic reticulum (ER). Furthermore, nearly 20% of the trispanins function in lipid metabolic processes and transport, which are also overrepresented. Nearly one-third of trispanins are identified as being targeted by drugs and/or being associated with diseases. A high number of 3TMs have unknown functions and based on this analysis we speculate on the functional involvement of uncharacterized trispanins in relationship to disease or important cellular activities. This first overall study of trispanins provides a unique analysis of a diverse group of membrane proteins.